2021
DOI: 10.1177/15589447211014603
|View full text |Cite
|
Sign up to set email alerts
|

Point Blank: A Retrospective Review of Self-inflicted Gunshot Wounds to the Hand

Abstract: Background A paucity of literature exists specifically examining self-inflicted (SI) gunshot wounds (GSWs) to the hand and wrist, which impart greater energy and have a higher risk of adverse events than non–self-inflicted (NSI) GSWs. Methods We retrospectively reviewed records of patients who presented to our plastic surgery service after sustaining acute GSWs involving the hand and wrist between 2016 and 2018. Results We identified 60 patients who sustained GSWs involving the hand and wrist; 17 (28%) were SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
4
2
0
Order By: Relevance
“…This is consistent with previous studies that have identified a greater incidence of SI GSWs to the hand [ 3 , 5 , 7 , 11 ]. Previous studies have examined specific injury locations within the hand and identified SI GSWs to be associated with the most distal structures (proximal phalanges) and NSI GSWs to be associated with more proximal structures (metacarpals) [ 3 , 7 ]. The current study examined injury locations across the entire upper extremity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is consistent with previous studies that have identified a greater incidence of SI GSWs to the hand [ 3 , 5 , 7 , 11 ]. Previous studies have examined specific injury locations within the hand and identified SI GSWs to be associated with the most distal structures (proximal phalanges) and NSI GSWs to be associated with more proximal structures (metacarpals) [ 3 , 7 ]. The current study examined injury locations across the entire upper extremity.…”
Section: Discussionsupporting
confidence: 93%
“…The NSI group also demonstrated a higher incidence of multiple wounds. This is consistent with previous studies and is most likely attributed to a violent context rather than an accidental discharge [ 3 , 5 ]. There was no difference in fracture rate between the groups with fractures occurring in 50–60% of the cases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations